2008
DOI: 10.1136/bjo.2007.135012
|View full text |Cite
|
Sign up to set email alerts
|

Practical recommendations for measuring rates of visual field change in glaucoma

Abstract: To date, there has been a lack of evidence-based guidance on the frequency of visual field examinations required to identify clinically meaningful rates of change in glaucoma. The objective of this perspective is to provide practical recommendations for this purpose. The primary emphasis is on the period of time and number of examinations required to measure various rates of change in mean deviation (MD) with adequate statistical power. Empirical data were used to obtain variability estimates of MD while stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
385
0
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(431 citation statements)
references
References 54 publications
9
385
0
15
Order By: Relevance
“…It is well established that interpretation of investigations is variable, a prime example in glaucoma being visual fields. 10 The relative independence of decision agreement from IOP variation within normal errors of estimate for a single reading suggests a wider use of available information in the decision-making process. Compliance, side effects and social situations are not always clearly documented in notes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that interpretation of investigations is variable, a prime example in glaucoma being visual fields. 10 The relative independence of decision agreement from IOP variation within normal errors of estimate for a single reading suggests a wider use of available information in the decision-making process. Compliance, side effects and social situations are not always clearly documented in notes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients recently diagnosed may need more frequent examinations to establish a baseline and rule out rapid progression. 14 It has recently been shown that three visual field examinations per year are required to detect a 4-dB change in mean deviation over 2 years with adequate statistical power. 14 The frequency of examination should also be increased if there is a higher perceived risk of functional visual loss, high IOP, visual field progression, or factors such as pseudoexfoliation, increased age, or family history of glaucoma blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Она зависит не толь-ко от факторов риска или формы глаукомы (рис.1), но еще от разных, не установленных пока обстоятельств [36]. Все это привело к одной очень важной рекоменда-ции по наблюдению за больными глаукомой: существует необходимость более частого выполнения периметрии (не реже трех раз в год в первые два года наблюдения) [37]. Проведенные исследования изменили саму пара-дигму мониторинга больных глаукомой.…”
Section: первые результатыunclassified
“…В последующем боль-шее внимание было уделено изучению скорости про-грессирования ГОН в клинической практике, т.е. на фоне лечения [32,33,37]. Можно сказать, что это -ключевой момент в мониторинге глаукомы, посколь-ку именно в этом случае удается определить риск сле-поты у конкретного больного, что отражено в Евро-пейских рекомендациях (European Glaucoma Society).…”
Section: какова скорость прогрессирования гон по результатам многоценunclassified